ARMA Models for Mortality Forecast - Šiškina, Natalja; Šiaulys, Jonas (Lithuanian Journal of Statistics, 2016)
In the last several decades, many countries have been paying a lot of attention to mortality forecastingbecause of high longevity risk. The purpose of this paper is to analyze mortality characteristics of Baltic countries andmake predictions using ARMA models. Research shoved that mortality rate distribution is almost the same in Lithuania, Latvia and Estonia and all of them represent longevity trends. It means that men and women, children and adults have thesame mortality structure in all Baltic countries and live longer than before.
Keywords: mortality forecasting; longevity risk; ARMA models